A intertextualidade na história em quadrinho “A turma do açaí” - DIAS, Jéssica Costa (2022)
This work presents an analysis of the intertextuality in the comic strips "A Turma do Açaí". Its purpose is to discuss the phenomenon of intertextuality in the comic strip “A gang of açaí”. Thus, the research is based on the theorists Kristeva (2005), Koch, Bentes and Cavalcante (2012), Marcuschi (2002) and Eisner (2005). In this sense, the work is based on descriptive research, having the comics of the “Turma do Açaí”, taken from the social network Facebook, as the corpus of the research. The results reveal that the comic strips of “A Turma do Açaí” have the presence of characteristics of the types of intertextuality of the restricted sense as the thematic, stylistic, explicit and implicit form, as well as the broad sense as the intergeneric and typological form. Thus, it can be concluded that the comics of the “Turma do Açaí” are related to other texts and that the perception of these intertextual relationships depends on the reader's prior knowledge of other texts and other cultural forms.